Kualitas Pelaporan Keuangan, Hutang Jangka Pendek dan Efisiensi Investasi - Susi Retna Cahyaningtyas; Wahidatul Husnaini; Zuhrotul Isnaini (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2019)
The quality of financial reporting and short-term debt affect investment efficiency. The more quality financial reporting shows there is no information asymmetry between managers and shareholders so that managers will make decisions that benefit shareholders, namely the efficiency of investment. Short-term debt is one mechanism to control the performance of managers. More use of short-term debt will reduce overinvestment and underinvestment. This study aims to empirically examine the effect of financial reporting quality and short-term debt on investment efficiency. The sample used in this study is a manufacturing company that went public on the Indonesia Stock Exchange in 2016 based on purposive sampling obtained a sample of 149 companies. The results showed that the financial reporting measurement model of Dechow and Dichev (2002) had an effect on investment efficiency. This means that the higher the financial reporting, the higher the investment efficiency. The quality of reporting models of McNichols and Stubben (2008) and short-term debt have no effect on investment efficiency. Short-term debt is not able to prove that the actions taken by management can be controlled by short-term debt so that it does not affect the efficiency of investment.